Enhancement Of Candida Rugosa Lipase Via Immobilization Onto Benzyltriethyl Ammonium Chloride-Modified Supports For The Synthesis Of Nonyl-Hexanoate - Hana Meftah Elgubbi
Studies have shown that kaolin clay has huge potentials to be utilized as excellent adsorbent and support for biocatalysts because they meet the requirement of today’s increasing eco-friendly demands of modern industries. Furthermore, they are inexpensive, microbial resistant, thermally stable and possesses appreciable mechanical strength. However, their use as support for biocatalysts immobilization are limited due to their hydrophilic nature. To overcome this, exchangeable cations (Na+) in their structures are replaced with quaternary ammonium cations (QACs) through ion exchange process. In this study, cation exchange capacity (CEC) by methylene blue method of natural kaolin and kaolin treated at 650 oC (metakaolin) were determined and found to be 2.5 meq/100g clay and 1.5 meq/100g clay, respectively. Benzyltriethylammonium chloride (BTEA-Cl) at varying concentrations (0.5 - 2.0x CEC of the natural kaolin and metakaolin) were used in the preparation of the organo-modified kaolin and organo-modified metakaolin. The organo-modified kaolin and metakaolin were characterized using X-ray diffractometer (XRD), Fourier transform infrared (FTIR) spectrometer, scanning electron microscope (SEM), and surface area and porosity analyzer. Successful organo-modifications of the natural kaolin were exhibited by the increase in d001 spacing from 7.12 Å to between 7.20 - 7.34 Å in XRD patterns. Similarly, successful conversion of kaolin to metakaolin as a result of thermal treatment was confirmed through the disappearance of kaolinite peak at 12.46°. XRD patterns of the modified and unmodified kaolin and metakaolin were found to be similar indicating the unchanged clay structures upon organo-modification with BTEA-Cl. Results of the successful modifications of kaolin and metakaolin were also exhibited by the appearance of major peaks in FTIR spectra at 2800–3000 cm-1 and 1474 cm-1 which represented the existence of CH stretching and aromatic C=C in BTEA+. The SEM micrographs of the organo-modified kaolin and metakaolin exhibited increasing individualized platelets and agglomeration as compared to the unmodified kaolin and metakaolin. Evidence of the organo-modification on natural kaolin and metakaolin was also noticed as surface areas of the clays showed drastic decrease from 25.34 m2/g natural clay to between 5.90 - 13.11 m2/g organo-modified clay, and from 19.91m2/g for metakaolin to between 9.04- 18.14m2/g for organo-modified metakaolin clays. The natural kaolin, metakaolin and their organo-modified counterparts were then used as supports in the immobilization of Candida rugosa lipase (CRL) via physical adsorption method. Organo-modified metakaolin with 2.0x CEC showed highest protein loading of up to 14.83 ± 1.37 mg protein/g clay and almost 70% of immobilization. Characterization of the immobilized lipases using XRD showed increased d001 spacing from 7.12 to 7.22 Å for kaolin, while d001 spacing of organo-modified kaolin decreased about 2%. SEM images exhibited substantial, thick and rough external surface as evidence of the existence of lipase on the surface of the kaolin and metakaolin clay. The absorption bands at 1656 cm-1, 1540 cm-1 were linked to the existence of CRL when identified using FTIR. Successful immobilization of CRL onto natural and organo-modified kaolin and metakaolin clay were also observed where surface areas and pore volumes decreased about 46%-72% and 1%-52%, respectively, while pore sizes of the clay increased about 42%-53% upon immobilization of CRL. The immobilized CRL, together with free CRL were then screened for esterification activities in the reactions which consisted of nonanol and hexanoic acid. CRL immobilized onto 2.0x CEC organo-modified natural kaolin (CRL-2.0 NK) and CRL immobilized onto 2.0x CEC organo-modified metakaolin (CRL-2.0 MK) showed 1.5 folds increased in activities as compared to free CRL. FTIR and gas chromatography-mass spectrometer (GC-MS) were used to confirm the successful synthesis of nonyl hexanoate using CRL immobilized onto the organo-modified clay. CRL-2.0 NK and CRL-2.0 MK also showed high thermal stabilities 57.67% and 51.39%, respectively even after incubation at 70 ℃. CRL-2.0 MK exhibited highest reusability where it maintained 65.15% of the initial activity (5.24×10-3 mmol ester/min/μg protein) even after 10 cycles of continuous uses. The abilities of the selected immobilized lipases (CRL-2.0 NK and CRL-2.0 MK) to synthesis the nonyl hexanoate were kinetically studied where kinetic parameters, Km and Vmax, were determined by means of Michaelis-Menten kinetic model and were best explained by the Ping-Pong Bi-Bi mechanism. The lower Km(Hex) values suggested that the CRL, CRL-2.0 NK and CRL-2.0 MK displayed higher affinity towards hexanoic acid (Hex) than towards nonanol (Non), Km(Non) > Km(Hex). The selected immobilized lipases also demonstrated considerably higher Vmax values (2.1786-2.3504 mmol/L/min) compared to free CRL (1.5810 mmol/L/min) in the enzymatic reaction. The present study had extensively explored the structure and physico characteristics of the different types of kaolin derivatives for their beneficial use as support for biocatalyst. Activities and stabilities of lipase immobilized onto the selected organo-modified clay were improved, suggesting that the preparation of functional immobilized biocatalyst are more adapted and practical substitute to the hazardous acid catalyst commonly used for nonyl hexanoate production.